PECULARITIES OF THE DEVELOPMENT OF WINERY ENTERPRISES UNDER UNCERTAIN ECONOMIC CONDITIONS IN UKRAINE - Yuriy DANKO; Anhelina HALYNSKA; Kseniia BLYUMSKA-DANKO; Volodymyr OREL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Conceptual provisions on the development of wineries in conditions of economic uncertainty are presented, which include: determining the adaptability, balance and effectiveness of the development of wineries; use of integrated assessments of balance as a basis for assessing the effectiveness of enterprises, which allows you to objectively develop directions for choosing a development strategy in accordance with business process indicators. It was proposed a scientific and conceptual approach to the development strategy of wineries in conditions of economic uncertainty, which, in contrast to the current, is based on the results of differentiated assessment of the level of development of wineries for different types of business processes in economic uncertainty and allows a reasonable choice of development strategy and identify a set of relevant strategic alternatives. Thus, for each winery should be defined tactical tasks for managing the development of wineries, based on certain coefficients of difficulty for the development of certain types of business processes of the winery. The integration of wineries development strategies with the strategic priorities of economic development in conditions of instability is presented in the matrix. Based on the presented matrix, it is determined that at the current level for balanced development of wineries development management priorities that meet the development strategy in conditions of economic uncertainty should be: overcoming the limited entry of domestic wine products into the domestic market, increasing international competitiveness and entering world markets; improving the quality of wines and ensuring a clear classification of their types and relevant technical requirements; improving the resource base for winemaking, streamlining the current regulatory framework; optimization of excise taxation; vertical integration of the industry; promoting the differentiation of approaches to regulating the activities of wineries in accordance with their size, insurance of crops and mutual funds, management of the varietal structure of vineyards, etc.